Managing smart 325 high-performance tips every manager must know - Milgram, Lynne (Cashman Dudley, 1999)
Examines the challenges facing today's management and provides fast, practical answers for solving common workplace situations. It presents step-by-step instructions for mastering more than 300 key real-world management tasks.